2013
DOI: 10.1371/journal.pone.0075412
|View full text |Cite
|
Sign up to set email alerts
|

Kinase Activity of ArcB from Escherichia coli Is Subject to Regulation by Both Ubiquinone and Demethylmenaquinone

Abstract: Expression of the catabolic network in Escherichia coli is predominantly regulated, via oxygen availability, by the two-component system ArcBA. It has been shown that the kinase activity of ArcB is controlled by the redox state of two critical pairs of cysteines in dimers of the ArcB sensory kinase. Among the cellular components that control the redox state of these cysteines of ArcB are the quinones from the cytoplasmic membrane of the cell, which function in ‘respiratory’ electron transfer. This study is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 30 publications
(40 reference statements)
6
31
2
1
Order By: Relevance
“…This culture was used as a 0.1% inoculum for 25 ml cell cultures which were grown as anaerobic batch culture at 37°C using Evans’ salt medium with nitrilo-acetic acid (2 mM) and sodium phosphate buffer (100 mM, pH 7) to increase buffering capacity (Evans et al, 1970; Sharma et al, 2013). Glucose (20 mM) was used as carbon source and 50 mM DMSO was used as terminal electron acceptor.…”
Section: Methodsmentioning
confidence: 99%
“…This culture was used as a 0.1% inoculum for 25 ml cell cultures which were grown as anaerobic batch culture at 37°C using Evans’ salt medium with nitrilo-acetic acid (2 mM) and sodium phosphate buffer (100 mM, pH 7) to increase buffering capacity (Evans et al, 1970; Sharma et al, 2013). Glucose (20 mM) was used as carbon source and 50 mM DMSO was used as terminal electron acceptor.…”
Section: Methodsmentioning
confidence: 99%
“…We observed accumulation of the reduced form of DsbA when LCFA-grown cells entered the stationary phase, which restored to the oxidized state in mid- and late-stationary phases of growth (Fig 4A). A previous study showed that during aerobic growth of E. coli (in minimal medium supplemented with glucose) an increase in cell density increases the ubiquinol/ubiquinone ratio due to a decrease in the availability of dissolved oxygen, and this ratio decreases later in stationary phase due to lowered metabolism [46]. Because LCFA metabolism produces a large number of electron donors, this would lead to a much larger increase in ubiquinol/ubiquinone ratio with an increase in cell density, thereby making ubiquinone less available for the oxidation of the disulfide bond-forming machinery.…”
Section: Discussionmentioning
confidence: 99%
“…These CH34 T clusters encode an RND system (czcICBA), the ZntA ATPase, a two-component regulatory system CzcRS and a 3-demethylubiquinone-9 3-methyltransferase (UbiG) [35,63]. UbiG participates in the biosynthesis of ubiquinone and its activity could be related to the sensor kinase activity of the twocomponent system CzcRS [78,79]. The czcL, hns and mmmQ genes encode an unknown protein, an H-NS like protein and a small stress responsive protein, respectively.…”
Section: P-type Atpase Proteinsmentioning
confidence: 99%